The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1074/jbc.m800328200
|View full text |Cite
|
Sign up to set email alerts
|

SOCS-3 Inhibits E2F/DP-1 Transcriptional Activity and Cell Cycle Progression via Interaction with DP-1

Abstract: Recent studies using SOCS family knock-out mice have suggested that SOCS proteins have multiple biological functions in addition to their role as negative regulators of JAK-STAT signaling. To explore these other functions of this family of proteins, we used yeast two-hybrid screening to find proteins interacting with human SOCS-3. We identified the transcriptional factor DP-1 as a SOCS-3-interacting protein involved in regulation of the cell cycle. Immunoprecipitation-Western blot assay showed that this intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Although specific interactions of SOCS1 with the transcription machinery of thioredoxin gene are not known, role of SOCS proteins as transcriptional factors have been suggested in recent studies (Baetz et al, 2008;Masuhiro et al, 2008). In particular, SOCS1 is found to interact with proto-oncogene FBI-1 (unpublished observations), which is involved in transcriptional regulation of tumor suppressor Rb as a potential mechanism to promote oncogenic potential (Jeon et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Although specific interactions of SOCS1 with the transcription machinery of thioredoxin gene are not known, role of SOCS proteins as transcriptional factors have been suggested in recent studies (Baetz et al, 2008;Masuhiro et al, 2008). In particular, SOCS1 is found to interact with proto-oncogene FBI-1 (unpublished observations), which is involved in transcriptional regulation of tumor suppressor Rb as a potential mechanism to promote oncogenic potential (Jeon et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Masuhiro and associates showed that SOCS-3 is an important key regulator in cell cycle progression (36). It is influenced by mutual interaction between SOCS-3 and the transcriptional factor DP-1.…”
Section: Cancer Researchmentioning
confidence: 99%
“…DP1 becomes ubiquitinated when deprived of the heterodimerization, although the adaptor for DP1 ubiquitination remains undefined (52). SOSC3 regulates the subcellular localization of DP1, and overexpression of SOSC3 resulted in cell cycle arrest (66). Our data revealed that DP1 was sequestered in the cytoplasm and coexpressed with E2F1 in the presence of Kbtbd5.…”
Section: Discussionmentioning
confidence: 63%